Higher-order aberrations and their association with axial elongation in highly myopic children and adolescents - Xu, Yupeng; Deng, Junjie; Zhang, Bo; Xu, Xian; Cheng, Tianyu; Wang, Jingjing; Xiong, Shuyu; Luan, Mengli; Zou, Haidong; He, Xiangui; Tang, Chun; Xu, Xun (British journal of ophthalmology, 2023)
BackgroundVision-dependent mechanisms play a role in myopia progression in childhood. Thus, we investigated the distribution of ocular and corneal higher-order aberrations (HOAs) in highly myopic Chinese children and adolescents and the relationship between HOA components and 1-year axial eye growth.MethodsBaseline cycloplegic ocular and corneal HOAs, axial length (AL), spherical equivalent (SE), astigmatism and interpupillary distance (IPD) were determined for the right eyes of 458 highly myopic (SE ≤−5.0D) subjects. HOAs were compared among baseline age groups (≤12 years, 13–15 years and 16–18 years). Ninety-nine subjects completed the 1-year follow-up. Linear mixed model analyses were applied to determine the association between HOA components, other known confounding variables (age, gender, SE, astigmatism and IPD) and axial growth. A comparison with data from an early study of moderate myopia were conducted.ResultsAlmost all ocular HOAs and few corneal HOAs exhibited significant differences between different age groups (all p<0.05). After 1 year, only ocular HOA components was significantly negative associated with a longer AL, including secondary horizontal comatic aberration (p=0.019), primary spherical aberration (p<0.001) and spherical HOA (p=0.026). Comparing with the moderate myopia data, the association of comatic aberration with AL growth was only found in high myopia.ConclusionIn highly myopic children and adolescents, lower levels of annual ocular secondary horizontal comatic aberration changes, besides spherical aberrations, were associated with axial elongation. This suggests that ocular HOA plays a potential role in refractive development in high myopia.